INOVASI PENGEMBANGAN BERUGAQ DENGAN MENGADOPSI ARSITEKTUR TRADISIONAL MELALUI DESAIN REVERSIBEL (INNOVATION IN BERUGAQ DEVELOPMENT BY ADOPTING TRADITIONAL ARCHITECTURE THROUGH REVERSIBLE DESIGN) - Audrey Maura; Vincentia Reni Vitasurya; Andi Prasetiyo Wibowo; Gregorius Agung Setyonugroho (Universitas Katolik Soegijapranata, 2026)
Traditional architecture in Lombok holds significant cultural value, particularly through the use of local timber and natural materials. However, lifestyle changes and the declining availability of traditional materials have led to the degradation of traditional buildings. This study responds to these challenges by proposing modifications that enhance structural performance while adopting reversible design principles to maintain cultural integrity. Focusing on the Berugaq structure in Bayan Village, North Lombok, the research aims to develop a sustainable and material-efficient modified Berugaq model that preserves traditional architectural values. A comparative case study method is used to assess traditional and modified Berugaq structures in terms of material efficiency, construction cost, installation practicality, and maintenance. Data collection includes field observations, physical measurements, cultural interviews, and 3D modeling. The findings show that adapting materials and connection systems—such as using standardized timber and practical steel-plate joints (bolt-on)—improves resource efficiency, reduces construction time, and simplifies maintenance without dismantling the entire structure. This study demonstrates how modern materials can be integrated into traditional architecture without compromising cultural meaning, offering a practical approach to preserving cultural heritage.